1976
DOI: 10.1159/000468217
|View full text |Cite
|
Sign up to set email alerts
|

Lorazepam and Diazepam in Anxious Outpatients

Abstract: The response of 134 anxious neurotic outpatients to lorazepam, diazepam, and placebo was assessed in a 4-week double-blind trial. Both active drugs produced significantly more symptom reduction than placebo. Lorazepam, however, proved effective primarily in those patients who did not complain of sedation, and produced greatest improvement in initially sicker patients. Sedation was significantly more disturbing to lorazepam-treated patients than to diazepam-treated patients. Present findings suggested that 3 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Jokinen et al (1984) found that a daily dose of I-2 mg flupentixol proved comparable with diazepam 5-10 mg daily, but their spectra of actions were somewhat different. Rickels et al (1976) used 3 mg lorazepam daily and concluded, after evaluation of the results, that this dose may be too high for mildly anxious patients. This conclusion is in agreement with our present data on the actions and concentrations measured after a single oral dose of 2.5 mg lorazepam.…”
Section: Discussionmentioning
confidence: 99%
“…Jokinen et al (1984) found that a daily dose of I-2 mg flupentixol proved comparable with diazepam 5-10 mg daily, but their spectra of actions were somewhat different. Rickels et al (1976) used 3 mg lorazepam daily and concluded, after evaluation of the results, that this dose may be too high for mildly anxious patients. This conclusion is in agreement with our present data on the actions and concentrations measured after a single oral dose of 2.5 mg lorazepam.…”
Section: Discussionmentioning
confidence: 99%